Fire Resistance of Geopolymer Foams Layered on Polystyrene Boards - Le, Van Su; Nguyen, Van Vu; Sharko, Artem; Ercoli, Roberto; Nguyen, Thang Xiem; Tran, Doan Hung; Łoś, Piotr; Buczkowska, Katarzyna Ewa; Mitura, Stanisław; Špirek, Tomáš; Louda, Petr (Polymers, 2022)
Geopolymer foams are excellent materials in terms of mechanical loads and fire resistance applications. This study investigated the foaming process of geopolymers and foam stability, with a focus on the fire resistance performance when using polystyrene as the base layer. The main purpose is to define the influence of porosity on the physical properties and consequently to find applications and effectiveness of geopolymers. In this study, lightweight materials are obtained through a process called geopolymerization. Foaming was done by adding aluminum powder at the end of the geopolymer mortar preparation. The interaction between the aluminum powder and the alkaline solution (used for the binder during the mixing process) at room temperature is reactive enough to develop hydrogen-rich bubbles that increase the viscosity and promote the consolidation of geopolymers. The basic principle of thermodynamic reactions responsible for the formation of foams is characterized by hydrogen-rich gas generation, which is then trapped in the molecular structure of geopolymers. The geopolymer foams in this study are highly porous and robust materials. Moreover, the porosity distribution is very homogeneous. Experimental assessments were performed on four specimens to determine the density, porosity, mechanical strength, and thermal conductivity. The results showed that our geopolymer foams layered on polystyrene boards (with optimal thickness) have the highest fire resistance performance among others. This combination could withstand temperatures of up to 800 °C for more than 15 min without the temperature rising on the insulated side. Results of the best-performing geopolymer foam underline the technical characteristics of the material, with an average apparent density of 1 g/cm3, a volume porosity of 55%, a thermal conductivity of 0.25 W/mK, and excellent fire resistance.
Keywords: silica sand; metakaolin; chopped basalt fibers; silica fume; aluminum powder; spray method; geopolymer foams; low thermal conductivity; high fire resistance